2016
DOI: 10.1080/14767058.2016.1236251
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Nrf2 deletion on placental morphology and exchange capacity in the mouse

Abstract: This data points out the necessity of functional Nrf2 for fetal and placental growth. A deficiency in Nrf2 signaling may negatively affect nutrient transfer capacity which is then no longer able to meet fetal growth demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
17
2
Order By: Relevance
“…Placental antioxidant status appears to play an important role in both placental adaptations to stress as well as in the maintenance of nutrient transfer capacity [45]. Hence, as expected, female placentas from ozone-exposed, placebo pregnancies (group 2) also demonstrated increases in a number of nutrient markers in the current study.…”
Section: Discussionsupporting
confidence: 75%
“…Placental antioxidant status appears to play an important role in both placental adaptations to stress as well as in the maintenance of nutrient transfer capacity [45]. Hence, as expected, female placentas from ozone-exposed, placebo pregnancies (group 2) also demonstrated increases in a number of nutrient markers in the current study.…”
Section: Discussionsupporting
confidence: 75%
“…We did not observe a significant reduction in birthweight of PBS-treated Nrf2 −/− mice. However, Nrf2 −/− mice were recently demonstrated to exhibit intrauterine growth restriction35. In our current study, PBS-treated Nrf2 −/− mice exhibited a slight delay in delivery compared to WT controls that was not significant and a slight decrease in birthweight that was not significant.…”
Section: Discussioncontrasting
confidence: 60%
“…Numerous reports demonstrated that Nrf2/Keap1 pathway activation played an important role in alleviating placental damage through inhibiting oxidative stress [52, 53]. A recent study found that weight and both total and labyrinth layer volume were significantly reduced in the placenta of Nrf2 knockout mice, highlighting deficiency in Nrf2 signaling impair placental development and dysfunction [54]. The present study found that the protein level of Keap1 was downregulated in OCA-treated pregnant mice, whereas the protein level of nuclear Nrf2 was upregulated in OCA-treated pregnant mice.…”
Section: Discussionmentioning
confidence: 99%